Expanding the Mitogen-Activated Protein Kinase (MAPK) Universe: An Update on MAP4Ks - Pan, Lixia; De Smet, Ive (Frontiers in Plant Science, 2020)
Phosphorylation-mediated signaling cascades control plant growth and development or the response to stress conditions. One of the best studied signaling cascades is the one regulated by MITOGEN-ACTIVATED PROTEIN KINASEs (MAPKs). However, MITOGEN-ACTIVATED PROTEIN KINASE KINASE KINASE KINASEs (MAP4Ks) are hardly explored. Here, we will give a comprehensive overview of what is known about plant MAP4Ks and highlight some outstanding questions associated with this largely uncharacterized class of kinases in plants.